Exploration of Ethnomathematics in Traditional Tea Processing in Banyumas as a Source of Mathematics Learning - Budi Lestari; Mohamed Bougeurra (Faculty of Tarbiya and Teacher Trainning, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2025)
This study explored ethnomathematics within the traditional tea processing in Banyumas Regency, aiming to examine its potential as a source for mathematics learning and its integration into instructional design. A qualitative ethnographic approach was employed at two sites: a home industry in Menggala Village, which processes raw tea leaves into semi-finished product, and another in Pasiraman Kidul Village, which refines semi-finished tea into consumable tea. Data were collected through interviews, observations, and documentation. Interviews were conducted with home industry owners to understand their techniques and knowledge related to mathematical concepts. Observations focused on daily activities, tools, and processes used in tea production. Findings revealed the presence of mathematical concepts such as geometry, measurement, ratios, decay, and set theory across various stages of tea production. Ethnomathematical activities identified included measuring ingredients, designing tools, counting quantities, determining optimal locations, and explaining procedures, which highlighted the relevance of traditional knowledge in mathematics education.